Хумалог: досвід клінічного застосування у дітей і підлітків із цукровим діабетом 1-го типу - Большова, О. В.; Самсон, О. Я. (Clinical Endocrinology and Endocrine Surgery, 2011)
The authors present the results of the use of an insulin analogue rapid-acting Humalog (lispro), in children and adolescents with type 1 diabetes mellitus. Humalog was found to be an effective, safe, and comfortable for the basal-bolus regimes of insulin therapy, that contributes to postprandial glycemic control. Humalog reduces glycolysated hemoglobin level, associates with decreasing of hypoglycemia incidence, especially at night, and improves patients' quality of life.